FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA INDUSTRI ROTI DI KABUPATEN ACEH BARAT (STUDI KASUS TOKO EVA KALORI) - Mahendra, Putra; Ariani, Dian; Yasrizal, Yasrizal; Ansari, Leli Putri (Universitas Teuku Umar, 2025)
This study examines the factors influencing labor productivity in the bread industry in West Aceh Regency, with a case study at Eva Kalori Bakery. Specifically, it analyzes the impact of wages and work experience as independent variables on productivity as the dependent variable. The study employs a qualitative approach using multiple linear regression analysis and primary data obtained through surveys with structured questionnaires distributed to employees. The aim is to identify whether wages and work experience, individually or simultaneously, have a significant effect on productivity. The results show that work experience has a positive and significant impact on labor productivity. Employees with longer work experience demonstrate higher productivity, highlighting the importance of knowledge and skills gained through experience. In contrast, wages do not significantly affect productivity, indicating that other factors, such as non-monetary incentives or workplace conditions, may play a more crucial role in motivating employees. When analyzed simultaneously, wages and work experience collectively have a significant effect on productivity, as evidenced by the F-test results